Bladder Cancer Diagnosis, Therapeutics, and Management - Lee, Cheryl T.; Wood, David P. (Current Clinical Urology, 2010)
In Bladder Cancer: Moving the Field Forward, Cheryl Lee, David Wood, and a panel of leading authorities and researchers provide a comprehensive review of the related literature, while providing insights into the obstacles of improved survival and discuss methods to advance the field of Bladder Cancer care. Their work aims to spur innovative thoughts and approaches to common problems in the management of early stage and advanced disease. The book discusses at length the state of bladder cancer staging and the optimal treatment for localized disease. Additional sections review the applications of existing systemic therapies and look at the infrastructure needed to support translational research efforts. Groundbreaking and authoritative, Bladder Cancer: Moving the Field Forward, is the definitive text on the current state of bladder cancer care and a must have for all urologists and medical oncologists who wish to provide their patients with the most comprehensive care.